2018
DOI: 10.1111/adb.12639
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability and therapeutic potential of the Mitragyna speciosa (kratom) alkaloids mitragynine and 7‐hydroxymitragynine

Abstract: Kratom, derived from the plant Mitragyna speciosa, is receiving increased attention as an alternative to traditional opiates and as a replacement therapy for opiate dependence. Mitragynine (MG) and 7-hydroxymitragynine (7-HMG) are major psychoactive constituents of kratom. While MG and 7-HMG share behavioral and analgesic properties with morphine, their reinforcing effects have not been examined to date. 7-HMG, but not MG, substituted for morphine self-administration in a dose-dependent manner in the rat self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
121
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 46 publications
4
121
2
2
Order By: Relevance
“…This is particularly concerning as there are no published clinical studies that describe the results of kratom administration for any of these therapeutic purposes. While animal models have indicated that the main component of kratom, mitragynine, has a low abuse potential [7,8], mitragynine may be metabolized into 7-hydroxymitragynine [9], a component of kratom with demonstrated abuse potential and drug dependency [10,11], exhibited analgesic effects that exceed the potency of morphine [12], and is a suspected adulterant of commercial kratom products [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly concerning as there are no published clinical studies that describe the results of kratom administration for any of these therapeutic purposes. While animal models have indicated that the main component of kratom, mitragynine, has a low abuse potential [7,8], mitragynine may be metabolized into 7-hydroxymitragynine [9], a component of kratom with demonstrated abuse potential and drug dependency [10,11], exhibited analgesic effects that exceed the potency of morphine [12], and is a suspected adulterant of commercial kratom products [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mitragynine exhibits polypharmacology in that it interacts with multiple central nervous system (CNS) drug targets . Thus, given these unique pharmacological mechanisms of action, mitragynine is considered an “atypical opioid.” Importantly, mitragynine has recently been reported to reduce morphine or heroin self‐administration without any abuse or addiction potential in rodent models . However, a minor, but potent μ‐opioid receptor agonist kratom alkaloid, 7‐hydroxymitragynine, exerts actions through β‐arrestin‐2 mediated pathways and produces tolerance and cross‐tolerance to morphine, in addition to physical dependence, which most likely contributes to the liabilities associated with kratom use .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given these unique pharmacological mechanisms of action, mitragynine is considered an “atypical opioid.” Importantly, mitragynine has recently been reported to reduce morphine or heroin self‐administration without any abuse or addiction potential in rodent models . However, a minor, but potent μ‐opioid receptor agonist kratom alkaloid, 7‐hydroxymitragynine, exerts actions through β‐arrestin‐2 mediated pathways and produces tolerance and cross‐tolerance to morphine, in addition to physical dependence, which most likely contributes to the liabilities associated with kratom use . Interestingly, another minor kratom alkaloid, corynantheidine, acts as a functional antagonist at μ‐opioid receptor and can reverse morphine‐induced inhibition of twitch contraction in pig ileum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[86] Mitragynine (85, Scheme 8), an indole alkaloid found in Kratom (Mitragyna spe-ciose korth), is am u-opioid agonist that hasr eceived attention as as afea lternative to traditional opiates (e.g.,m orphine) and as ar eplacement therapy for opiate dependence. [91][92][93][94][95][96] In addition, iboga root extracts were found to alleviateo piate withdrawals ymptoms, [97,98] whichh as initiated work to use iboga as at reatment for addiction. [99] Ibogaine (99,S cheme 9) is the active pharmacological substance of the iboga root and shares tryptophan/isoprenoid biosynthetic origins with all other monoterpenoid indole alkaloids.…”
Section: Indole Alkaloids:b Iosynthesis and Biological Activitiesmentioning
confidence: 99%